2017
DOI: 10.1111/jsap.12695
|View full text |Cite
|
Sign up to set email alerts
|

Serum thyroxine and thyroid‐stimulating hormone concentration in hyperthyroid cats that develop azotaemia after radioiodine therapy

Abstract: OBJECTIVES : The objectives of this study were to determine which serum thyroid hormone test best identifies iatrogenic hypothyroidism in cats that develop azotaemia after radioiodine treatment and to determine which thyroid test best differentiates these azotaemic, hypothyroid cats from azotaemic, radioiodine-treated euthyroid cats, as well as from azotaemic cats with chronic kidney disease and no history of thyroid disease. M ATERIALS AND M ETHODS : A total of 42 hyperthyroid cats that developed azotaemia (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
76
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(83 citation statements)
references
References 75 publications
5
76
2
Order By: Relevance
“…Our study confirmed that cats with iatrogenic hypothyroidism are more likely to become azotemic than cats that remain euthyroid . Additionally, the proportion of cats that develop azotemia after treatment for hyperthyroidism depends, at least in part, on the degree to which the hyperthyroidism is controlled (ie, how low the serum T 4 falls) .…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Our study confirmed that cats with iatrogenic hypothyroidism are more likely to become azotemic than cats that remain euthyroid . Additionally, the proportion of cats that develop azotemia after treatment for hyperthyroidism depends, at least in part, on the degree to which the hyperthyroidism is controlled (ie, how low the serum T 4 falls) .…”
Section: Discussionsupporting
confidence: 78%
“…Direct GFR measurements have not been reported in hypothyroid cats—neither before nor after levothyroxine replacement—but those studies are needed. We recently reported, however, that levothyroxine can lower serum creatinine concentrations in 131 I‐induced (iatrogenic) hypothyroid cats with moderate azotemia, but we know of no studies on the effect of levothyroxine on serum SDMA concentrations in hypothyroid cats—additional studies are again needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations